263 EVALUATION AND SCORE ASSESSMENT OF SUBSTANCE ABUSE AND PSYCHOSOCIAL HISTORY TO DETERMINE RECIDIVISM RISKS IN LIVER TRANSPLANT PATIENTS. (10th December 2015) - Deane, K.; Talamantes, M.; Trotter, J.
Abstract : Purpose: To determine the rate of recidivism to substance abuse in liver transplant recipients, as well as risk factors for recidivism that could be used to evaluate liver transplant candidates in the future. Methods: A retrospective review of 546 patients' pre-transplant psychosocial evaluations was used to determine liver disease etiology, transplant date and date of death (if applicable), and to devise a scoring system to assess pre-transplant risk factors that were associated with post-transplant recidivism. A score of 0, 1 or 2 was assigned to patients for the following areas; social support, finances, alcohol and drug abuse, and psychiatric history. After score assessment, a list of known recidivism patients was obtained and their scores were compared to non-recidivism patients to ascertain if the scores were valid ways to evaluate recidivism risks. Results: The study population was typical for OLT patients, the most common etiology of liver disease being hepatitis C (35%). The rate of recidivism was 20/544 (3.7%). The only pre-transplant risk factor that was more common in patients with recidivism was pre-transplant alcohol abuse. The mean total risk factor score was also significantly higher for the recidivism population (3.0) vs. patients without recidivism (1.8) p≤0.05. (figure ) Conclusions: 1) Recidivism is relatively uncommon in liver transplant recipients. 2) Predicting post-transplant recidivism was difficult; the only pre-transplant risk factor that was predictive of post-transplant recidivism was pre-transplant alcohol abuse.